Pregnancy Outcome between Booked and Unbooked Cases in A Tertiary Level Hospital - Adhikary, Alpana; Begum, Anwara; Joty, Fahmida Sharmin; Sarker, Nihar Ranjan; Akhter, Tahmina (Journal of Shaheed Suhrawardy Medical College, 2018)
To achieve the Sustainable Development Goals (SDG’2030) with regards to maternal health, there is need for research on the local causes and factors influencing adverse maternal & foetal outcomes in health institutions. Antenatal care throughout the pregnancy can ensure better feto-maternal outcome. It also contributed to reduction of maternal and infant mortality. This study was an attempt to enable health care providers to know where to focus to overcome adverse maternal outcome. Objectives: To find out the difference in maternal and perinatal outcome and socio-demographic characteristics in booked and unbooked cases. Design: A Cross-sectional observational study. Place of study :Department of Obststrics and Gynaeology , Shaheed Suhrawardy Medical College Hospital. Study period: April’2015 to july’2015. Study population- All patients admitted for delivery and puerperium during study period. Results: Unbooked mothers constituted 39.1% of the 218 deliveries in the studied period. There was no mean age difference between booked mothers and unbooked mothers (26.05±5.5 and 25.44±5.4; P=0.667) .But unbooked cases had a lower educational status (P<0.0036). Majority of the unbooked cases were from low family income group. Unbooked mothers were about less likely to deliver by spontaneous vaginal delivery compared to booked mothers (28% to 39%; P<0.339) and more likely to be delivered by emergency caesarean section than booked mothers. Unbooked mothers were having low birth weight babies than booked mother (2.65±0.595 and 3.02±0.477, p<0.010). Referral to neonatal unit more common in unbooked cases (69.6% to 25.6%). Post partum complications in unbooked and booked cases were (44%and 20.5%). Conclusion: The study showed a positive correlation between socio –demographic factor and lack of proper antenatal care and adverse pregnancy outcome. Improving the availability and accessibility of quality antenatal and delivery care services in all our institutes will improve pregnancy outcome. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 43-48